Gestión financiera y el capital de trabajo en las gasolineras segmento combustible - Fuentes Alvarado, Luis Enrique (2022)
The management and control of cash is a company is an activity that must be executed as a reviewer of operations that generate cash of which it is important to keep up to date to provide accurate information to management to know what is the liquidity of which is It has up to date and can also make projections in the short, medium and long term, depending on the income and the projection of expenses. Due to the naturalization of COGASOIL's business, which is a gas station, operations are mostly in cash, the objective of the investigation being to analyze how financial management affects the Fuel Segment working capital in the city of Guayaquil. In the study carried out, it was evidenced the activities carried out by the collaborators in the fuel distribution part, as well as the internal administrative management with respect to the accounting balances and the internal management of the money, through a qualitative and quantitative investigation with the tools interview and survey…….